Patient‐reported swallowing function after treatment for early‐stage oropharyngeal carcinoma: Population‐based study. Issue 8 (6th March 2020) - Karsten, Rebecca T.; van den Brekel, Michiel W.M.; Smeele, Ludi E.; Navran, Arash; Leary, Sam; Ingarfield, Kate; Pawlita, Michael; Waterboer, Tim; Thomas, Steve J.; Ness, Andy R.
Abstract: Background: Single‐modality treatment (surgery or radiotherapy [RT]) is a curative treatment option for early‐stage oropharyngeal carcinoma (OPC) with comparable (excellent) oncological outcomes. This study aimed to compare self‐reported swallowing function. Methods: Participants with a T1‐2N0‐2bM0 OPC who were offered single‐modality treatment and were recruited to the Head and Neck 5000 study were included. Prospectively collected self‐reported swallowing function was compared between surgery and RT. Results: Those offered RT (n = 150) had less favorable baseline characteristics than those offered surgery (n = 150). At 12‐month follow up, RT participants reported more swallowing problems (35% vs 23%, RR 1.3; 95% CI 0.8‐2.3, P = .277) in models adjusted for baseline characteristics. In those allocated to surgery who received adjuvant therapy (n = 78, 52%), the proportion with swallowing problems was similar to those allocated to RT alone. Conclusions: Participants offered surgery alone had similar mortality but improved swallowing, although this was not statistically significant. However, over half of participants offered surgery alone received surgery and adjuvant therapy.